Metformin and its sulphonamide derivative simultaneously potentiateanti-cholinesterase activity of donepezil and inhibit beta-amyloid aggregation - Magdalena Markowicz-Piasecka; Kristiina M. Huttunen; Joanna Sikora (Taylor & Francis Group, 2018)
The aim of this study was to assess in vitro the effects of sulphenamide and sulphonamide derivatives of metformin on the activity of human acetylcholinesterase (AChE) and butyrylcholinesterase (BuChE), establish the type of inhibition, and assess the potential synergism between biguanides and donepezil towards both cholinesterases (ChEs) and the effects on the β-amyloid aggregation. Sulphonamide 5 with para-trifluoromethyl- and ortho-nitro substituents in aromatic ring inhibited AChE in a mixed-type manner at micromolar concentrations (IC50 = 212.5 ± 48.3 µmol/L). The binary mixtures of donepezil and biguanides produce an anti-AChE effect, which was greater than either compound had alone. A combination of donepezil and sulphonamide 5 improved the IC50 value by 170 times. Compound 5 at 200 µmol/L inhibited Aβ aggregation by ∼20%. In conclusion, para-trifluoromethyl-ortho-nitro-benzenesulphonamide presents highly beneficial anti-AChE and anti-Aβ aggregation properties which could serve as a promising starting point for the design and development of novel biguanide-based candidates for AD treatment.